2022
DOI: 10.1186/s12890-022-01840-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the sarcopenia screening in older patients with interstitial lung disease

Abstract: Background The Asian Working Group for Sarcopenia 2019 (AWGS 2019) is the gold standard diagnostic criteria for sarcopenia in Asian populations. The calf circumference (CalF), the strength, assistance in walking, rising from a chair, climbing stairs, and falls (SARC-F) and the SARC-CalF questionnaires for sarcopenia screening have been used by AWGS 2019. The aim of this study was to assess accuracy of these three sarcopenia screening tools in patients with interstitial lung disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…A recent study by Hanada et al . applied the diagnostic criteria of the Asian Working Group for Sarcopenia 2019 in a cohort of 78 patients with interstitial lung diseases (ILD) of Asian ethnicity and observed a prevalence of sarcopenia of 32%, higher than the one we observed in our cohort of patients with IPF at diagnosis [ 12 ]; however, these differences may be due to the different ethnicity of the study population (in our study all patients were Caucasian) and to the different underlying pulmonary disease. On the contrary, Bocchino et al .…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…A recent study by Hanada et al . applied the diagnostic criteria of the Asian Working Group for Sarcopenia 2019 in a cohort of 78 patients with interstitial lung diseases (ILD) of Asian ethnicity and observed a prevalence of sarcopenia of 32%, higher than the one we observed in our cohort of patients with IPF at diagnosis [ 12 ]; however, these differences may be due to the different ethnicity of the study population (in our study all patients were Caucasian) and to the different underlying pulmonary disease. On the contrary, Bocchino et al .…”
mentioning
confidence: 63%
“…Recent literature has evaluated the prevalence of dynapenia and sarcopenia in patients with fibrosing interstitial lung diseases at various stages [ 12 14 ].…”
mentioning
confidence: 99%
“…Regarding interstitial lung disease (ILD), it is reported that sarcopenia was identified in 32.1% of Japanese patients with ILD. 19 In patients with IPF, the reported muscle assessments were the fat-free mass index, 20 ASMI, 21 and cross-sectional area of the erector spinae muscles. [22][23][24][25][26] A lower skeletal muscle mass is associated with lower quality of life and worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, among all reported sarcopenia screening models, ours showed the highest performance (AUC 0.988, 95% CI 0.986-0.989) [25,33,51,52]. We have developed a pipeline involving both deep-learning-and machine-learning-based models, to take both radiographic images and patient baseline characteristics into consideration (which can be easily obtained in the preoperative clinical setting).…”
Section: Discussionmentioning
confidence: 99%